Governance Challenges During the COVID-19 Pandemic in Africa - Dorasamy, Nirmala (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This book presents insights into the governance challenge associated with the management of the lockdown measures in relation to the welfare of citizens in selected African states. The intention of the project is to present a critical analysis of the effectiveness and the consequences of the measures adopted by the government of these African countries to contain further spread of the virus, within the context of existing governance challenges in the management of the public sector. This will expose the contradictions in the implementation of public policy and the actualization of its intendment for the promotion of good governance and the welfare of citizens. The benefit thereof is the feasibility of arousing further intellectual engagements on the need for effective management of public sector with strong infrastructural support for the good of all in Africa. Nirmala Dorasamy is an NRF rated Professor in the Department of Public Management and Economics at the Durban University of Technology (DUT), Durban, South Africa.
Introduction -- Chapter One: Governance challenges in the Public Sector Management in Africa -- Chapter Two: COVID-19 and Social Alteration Challenges -- Chapter Three: Devastating Economic Challenges and Potential Opportunities of COVID-19 pandemic in the Petroleum Industry Sector of the Democratic Republic of Congo (DRC) -- Chapter Four: Reinvigorating the Okavango Delta Through E-Tourism and Localization- Chapter Five: The syndemic of HIV, gender inequality and poverty during the COVID-19 pandemic among women in South Africa -- Chapter Six: COVID-19 Regulations and the Inequality Gap in Education and Housing in South Africa -- Chapter Seven: Covid-19, Poverty, and Inequality: Implication on the Egyptian Economy -- Chapter Eight: Covid-19 ramifications in Lesotho: A poverty perspective -- Chapter Nine: Livelihoods or Health? The contradictions and socio-economic impact of Covid-19 Lockdown on informal traders in Harare, Zimbabwe -- Chapter Ten: Poverty and Inequality as Sources of Community Fragility during COVID-19 Lockdown in Zimbabwe's Urban Spaces -- Chapter Eleven: Reinforcing Governance Imperatives in post-COVID-19 Africa. .
Keywords: Africa-Politics and government; African Politics